О НЕКОТОРЫХ ВОПРОСАХ ПОНЯТИЯ ПУБЛИЧНЫХ ФИНАНСОВ - Сосна, Александр (SUPREMANCE OF LAW, 2017)
In its submission the author examines the theoretical and legal characterization of public finances, which are an important and fundamental part of the subject of financial law. The author analyzes in comparative terms of the theoretical aspects of the concept of “public finances”. Noteworthy are the conclusions and suggestions expressed by the author in the scientific and practical study of the concept and content of the public fi nances.